2018
DOI: 10.1111/cns.12835
|View full text |Cite
|
Sign up to set email alerts
|

Brain structure alterations in depression: Psychoradiological evidence

Abstract: Depression is the leading cause of disability around the world, but little is known about its pathology. Currently, the diagnosis of depression is made based on clinical manifestations, with little objective evidence. Magnetic resonance imaging (MRI) has been used to investigate the pathological changes in brain anatomy associated with this disorder. MRI can identify structural alterations in depressive patients in vivo, which could make considerable contributions to clinical diagnosis and treatment. Numerous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
210
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 340 publications
(223 citation statements)
references
References 104 publications
(216 reference statements)
9
210
1
3
Order By: Relevance
“…Much of the neurobiology of major depression is unknown, but subtle alterations of brain structure may be involved, and various MRI-based studies have observed regional brain differences between individuals with major depression and healthy control subjects. A recent review of the literature by Zhang et al (4) described various possible structural alterations in the brains of individuals with major depression, such as case-control differences in the thickness of the medial orbitofrontal cortex and inferior parietal gyrus. However, it was also noted that the results of structural MRI studies in major depression have often been inconsistent (4).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Much of the neurobiology of major depression is unknown, but subtle alterations of brain structure may be involved, and various MRI-based studies have observed regional brain differences between individuals with major depression and healthy control subjects. A recent review of the literature by Zhang et al (4) described various possible structural alterations in the brains of individuals with major depression, such as case-control differences in the thickness of the medial orbitofrontal cortex and inferior parietal gyrus. However, it was also noted that the results of structural MRI studies in major depression have often been inconsistent (4).…”
mentioning
confidence: 99%
“…A recent review of the literature by Zhang et al (4) described various possible structural alterations in the brains of individuals with major depression, such as case-control differences in the thickness of the medial orbitofrontal cortex and inferior parietal gyrus. However, it was also noted that the results of structural MRI studies in major depression have often been inconsistent (4). This inconsistency is likely due to the use of small study sample sizes in relation to subtle effects, as well as heterogeneity among studies in terms of clinical characteristics and methodology; for example, hardware and software differences between scanners and distinct data processing pipelines can contribute to heterogeneity (5).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We assembled four review articles. In the first review article, Zhang et al systematically reviewed recent neuroimaging studies regarding significant structural alterations in brain regions and circuits in patients with major depressive disorder (MDD). They highlighted regional gray matter (GM) changes in several crucial regions in MDD, including the frontal lobe (mainly parts of the anterior cingulate, orbitofrontal, and dorsolateral prefrontal cortices), the thalamus, the striatum, the parietal lobe, and the hippocampus.…”
mentioning
confidence: 99%